Triatoma maculata, the Vector of Trypanosoma cruzi, in Venezuela. Phenotypic and Genotypic Variability as Potential Indicator of Vector Displacement into the Domestic Habitat - García-Alzate, Roberto; Lozano-Arias, Daisy; Reyes-Lugo, Rafael Matías; Morocoima, Antonio; Herrera, Leidi; Mendoza-León, Alexis (Frontiers in Public Health, 2014)
ABSTRACT Triatoma maculata is a wild vector of Trypanosoma cruzi, the causative agent of Chagas disease; its incursion in the domestic habitat is scant. In order to establish the possible domestic habitat of T. maculata, we evaluated wing variability and polymorphism of genotypic markers in subpopulations of T. maculata that live in different habitats in Venezuela. As markers we used the mtCyt b gene, previously apply to evaluate population genetic structure in triatomine species, and the β-tubulin gene region, a marker employed to study genetic variability in Leishmania subgenera. Adults of T. maculata were captured in the period 2012-2013 at domestic, peridomestic and wild areas of towns in the Venezuelan states of Anzoátegui, Bolívar, Portuguesa, Monagas, Nueva Esparta and Sucre. The phenotypic analysis was conducted through the determination of the isometric size and conformation of the left wing of each insect (492 individuals), using the MorphoJ program. Results reveal that insects of the domestic habitat showed significant reductions in wing size and variations in anatomical characteristics associated with flying, in relation to the peridomestic and wild habitats. The largest variability was found in Anzoátegui and Monagas. The genotypic variability was assessed by in silico sequence comparison of the molecular markers and PCR-RFLP assays, demonstrating a marked polymorphism for the markers in insects of the domestic habitat in comparison with the other habitats. The highest polymorphism was found for the β-tubulin marker with enzymes BamHI and KpnI. Additionally, the infection rate by T. cruzi was higher in Monagas and Sucre (26.8 and 37.0% respectively), while in domestic habitats the infestation rate was highest in Anzoátegui (22.3%). Results suggest domestic habitat colonization by T. maculata that in epidemiological terms, coupled with the presence in this habitat of nymphs of the vector, represents a high risk of transmission of Chagas disease.